Determining the investment attractiveness of the biohacking and bioinnovation market based on market trends in the pharmaceutical business - Andriushchenko, Anhelina; Liezina, Anastasiia; Kolybo, Denis; Gurina, Ganna; Havrysh, Kostiantyn; Mazur, Nataliya; Kushnir, Oksana; Kyryliuk, Oksana (Technology audit and production reserves, 2026)
The object of the study was the process of venture investment in biohacking as a component of the pharmaceutical business, which embodies the development of the specified market. Since research requires significant capital investments, it is worth studying in detail and carefully the issues of financial investments and obtaining income from the specified processes. This work proposes a comprehensive economic analysis of the biohacking industry as a modern investment tool. The consistency of the high growth forecast with the main statistical risks inherent in biotechnology enterprises was described and analyzed. The basis for the hypothesis was the methodology for analyzing the development of the biohacking investment market. The analysis is based on the success rates of clinical trials and the development of FDA medical products from phase I to approval. The results are based on an assessment of the capital market of biotechnology companies in the world after IPOs since 2020. The results confirmed the hypothesis of rapid market growth with a compound annual rate of 19.09% from 2025 to 2034 (forecast). However, there is a rather low overall clinical success rate, about 9.06% between phase I and final drug approval, considering the highest percentage of research outflow between phases II and III (only 31% success). The best value was obtained for rare diseases (about 25.0%), the worst for oncology research (5.1%). The results indicate that most of the investments (about 56%) end in loss. As a result, it was determined that biohacking is currently a high-risk and at the same time highly productive direction, which has a radically different nature of investment. That is why investment should be based on careful, substantiated, reliable data analysis and assessment of the clinical portfolio, considering diversified risks.